Willis's elements of quantity surveying - Lee, Sandra Jean; Willis, Andrew; Trench, William (Chichester, West Sussex, United Kingdom : Wiley/Blackwell, 2014)
Setting down the measurement process from first principles and covering the main building elements, this edition of the classic text considers computerised measurement techniques using standard descriptions.
Based on an original work: Elements of quantity surveying / Arthur James Willis. 1935.
Includes index.
oif 17/12/2019
Loans
Keywords: Building; Quantity surveying